Implementation the Concept of Restorative Justice in the Settlement of Special Crimes of Trademark Counterfeiting - Zaky Naufal Dahana; Emilda Kuspraningrum; Setiyo Utomo; Bakhouya Driss (RechtIdee, 2025)
The promulgation of Law Number 20 of 2016 concerning Marks and Geographical Indications against the law only leads to defendants who are finally subject to apparent imprisonment for the act of counterfeiting the mark has brought harm to the victim, preferably for The act of counterfeiting the brand attached to it is a criminal sanction for the application of the concept of Restorative Justice which focuses on the conditions of creating justice and balance for criminal offenders and victims with restoration which is a restoration of rights between victims and perpetrators. The research method used in this study is doctrinal, with source material in primary, secondary, and tertiary legal materials. This study resulted in two advantages of using Restorative Justice on the specific crime of trademark forgery. First, Restorative Justice can be a policy choice for law enforcement officials. Because the interests of victims need to be considered in the process. In addition, Intellectual Property Rights are the realm of economics or business where the victim must suffer a large loss if there is a violation. Second, law enforcement against specific criminal acts of trademark rights through Restorative Justice can be a criminal law reform which is an alternative way to carry out punishment with the aim of justice.